An Evaluation of a Fluorescence In Situ Hybridization Strategy Using Air-dried Blood and Bone-marrow Smears in the Risk Stratification of Pediatric B-Lineage Acute Lymphoblastic Leukemia in Resource-limited Settings. Issue 4 (May 2021) - Sharma, Praveen; Rana, Sonia; Sreedharanunni, Sreejesh; Gautam, Arambam; Sachdeva, Man Updesh Singh; Naseem, Shano; Varma, Neelam; Jain, Richa; Bansal, Deepak; Trehan, Amita
Abstract : Cytogenetic abnormalities (CAs), one of the strongest influencers of therapeutic outcome in pediatric B-cell precursor acute lymphoblastic leukemia (BCP-ALL), can be identified by different techniques. Despite several technological advances, many centers with resource-limited settings continue to use either reverse-transcriptase polymerase chain reaction (RT-PCR) and/or fluorescence in situ hybridization (FISH) to identify prognostically relevant CAs. We evaluated a simple and cost-effective triple-probe FISH strategy on air-dried blood and bone-marrow smears and compared its performance with a multiplex RT-PCR-based approach in the prognostication of pediatric BCP-ALL patients. Three hundred twenty BCP-ALL patients were tested prospectively and in parallel by FISH on air-dried blood or bone-marrow smears and RT-PCR. The FISH strategy correctly diagnosed all genetic abnormalities identified by RT-PCR. Prognostically relevant genetic abnormalities were missed by RT-PCR in 24 (8.1%) patients. In another 20 children (6%), with samples inadequate for RT-PCR testing (dry taps or due to poor sample quality), a successful FISH testing could be performed on bone-marrow aspirate or trephine-imprint smears. In addition, FISH detected ploidy changes, which could be confirmed by FxCycle Violet-based flow-cytometry. FISH testing on air-dried smears identified more prognostically relevant CAs, provided information on the ploidy status, and could be successfully performed in children with difficulty in bone-marrow sampling.